Gaya Kepemimpinan Pendidikan dalam Novel Merindu Baginda Nabi karya Habiburrahman El-Shirazy - Nurananda, Nurananda; Taufiqurrahman, Taufiqurrahman; Nurfadilah, Intan; Asyari, Hasyim; Ratnaningsih, Sita (LPPM Universitas Mohammad Husni Thamrin, 2022)
The purpose of this study is to find out what leadership styles are in the novel Merindu Baginda Nabi. The background of this research is to examine what leadership styles are contained in the novel Merindi Baginda Nabi and how to practice them. The method used in this study is a qualitative type of literature (library research), which is a type of research that refers to the literature of literature such as book literature, articles and e-journals. The results show that there are 9 leadership styles in the novel Merindu Baginda Nabi by Habiburrahman El Shirazy, namely: Supportive Leadership Style, Democratic Leadership Style, Educational Leadership Style, Persuasive Leadership Style, Innovative Leadership Style, Motivative Leadership Style, Charismatic Leadership Style, Fatherly Leadership Style , and Participatory Leadership Style. Because novels can be an educational tool or facility in the process of leadership formation, with novels leaders can learn a lot about leadership styles.